Prospective History Teachers' Experiences in Place-Based Education: A Qualitative Study on the Development of Social-Emotional Skills - Bonita Padang; Dyah Kumalasari; Malik Salim (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
21st-century education requires teachers to be not only cognitively competent but also to have mature social-emotional skills, especially for prospective history teachers in facilitating historical empathy and managing sensitive discussions. Place-Based Education (PBE) offers a contextual learning approach that links historical material to local places and communities, thereby potentially serving as a vehicle for developing social-emotional skills through authentic learning experiences. This study aims to examine the application of Place-Based Education to develop the social-emotional skills of prospective history teachers. The research uses a qualitative approach, with data collected through learning observations, interviews, and documentation. The results show that place-based learning creates authentic learning experiences that encourage the development of relational skills, responsible decision-making, self-management, and social and self-awareness among students through direct interaction and contextual reflection. These findings conclude that Place-Based Education is a relevant pedagogical approach for integrating history learning with the development of social-emotional competencies in prospective history teachers.